Singaporean Perspectives: Attitudes and understanding of DEI in the Workplace - Bin Samad, Muhammad Riduan (Center for Southeast Asian Social Studies (CESASS), 2025)
This study explores Singaporeans’ attitudes and understanding of Diversity, Equity, and Inclusion (DEI) in the workplace, focusing on inclusiveness, respect, and belonging. An online survey of 94 participants across industries found that most viewed their organisations as inclusive, with DEI activities significantly enhancing employees’ sense of belonging. However, gaps remain in disability inclusion and support for non-native English speakers. While Chinese Singaporeans reported slightly higher levels of respect than Minority Singaporeans (Malay, Indian, and Others), the difference was not statistically significant, suggesting other factors, such as unconscious biases or workplace dynamics, may influence perceptions. Singapore’s multicultural education system, which promotes racial equality, may also minimise ethnicity’s role in workplace respect. This study addresses the scarcity of DEI research in Asia and provides recommendations for organisations and policymakers to strengthen DEI strategies for more inclusive workplaces.